2019
DOI: 10.1039/c9fo01186b
|View full text |Cite
|
Sign up to set email alerts
|

Faba bean protein flours added to pasta reduce post-ingestion glycaemia, and increase satiety, protein content and quality

Abstract: Durum Wheat Semolina (DWS) pastas with added fababean (FB) protein flour reduce postprandial blood glucose and appetite and have higher nutritional quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 33 publications
1
19
0
Order By: Relevance
“…Faba bean flour and protein concentrate were added to pasta (25% dwb) and fed to 15 human subjects and compared to a durum semolina pasta. Pasta with faba bean added had reduced postprandial blood glucose response and improved satiety with acceptable sensory liking for the faba bean flour pasta [ 125 ]. Greffeuille et al (2015) [ 126 ] over a two and a half month period fed 15 healthy subjects cooked durum wheat pasta dried at a low temperature (control), and pasta enriched with 35% faba bean dried at either a low or very high temperature and the GI was determined and visual analogue scale (degree of fullness).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Faba bean flour and protein concentrate were added to pasta (25% dwb) and fed to 15 human subjects and compared to a durum semolina pasta. Pasta with faba bean added had reduced postprandial blood glucose response and improved satiety with acceptable sensory liking for the faba bean flour pasta [ 125 ]. Greffeuille et al (2015) [ 126 ] over a two and a half month period fed 15 healthy subjects cooked durum wheat pasta dried at a low temperature (control), and pasta enriched with 35% faba bean dried at either a low or very high temperature and the GI was determined and visual analogue scale (degree of fullness).…”
Section: Resultsmentioning
confidence: 99%
“…Inulin (a prebiotic) addition to pasta has been shown in laboratory studies to lower starch digestion up to ~5% inclusion [ 53 ] and at higher levels > 7.5% [ 54 ] backed up by clinical studies showing 11% inulin pasta slows the gastric emptying causing a decrease in PPGR [ 24 ]. Clinical studies adding flours from chickpea [ 91 , 129 ], faba bean [ 125 , 126 ], lupin [ 92 ] and red lentil flour [ 130 ] to pasta show reductions in GI. Laboratory studies with these flour additions to pasta support reduction in GI [ 61 ] while similar in vitro studies in faba bean are lacking and only one study looked at pasta fortified with lupin protein isolate (17%) showing a reduction in in vitro starch digestion [ 66 ].…”
Section: Resultsmentioning
confidence: 99%
“…While it is relatively easy to add a concentrated form of protein into a shake, juice or smoothie (the given source was the only source of protein), the addition of protein to a solid food usually requires an additional filler, such as wheat flour, which is also a source of additional protein. Although this is a commonly used and understandable study protocol, since proteins are not consumed in isolation and are designed to be a potential functional ingredient, it was also one of the reasons why some valuable findings could not be included in the analysis [70][71][72]. In those studies authors investigated the effects of fava bean protein concentrate and isolate [70,71], and pea protein isolate [72], added to pasta, crackers and habitual diet (respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Although this is a commonly used and understandable study protocol, since proteins are not consumed in isolation and are designed to be a potential functional ingredient, it was also one of the reasons why some valuable findings could not be included in the analysis [70][71][72]. In those studies authors investigated the effects of fava bean protein concentrate and isolate [70,71], and pea protein isolate [72], added to pasta, crackers and habitual diet (respectively). The results revealed that the addition of fava bean protein to pasta reduced postprandial glycaemia and appetite, increased PYY and C-peptide responses, however, with significant effects on plasma insulin or GLP-1 [70].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation